Supporting the Declaration of Casablanca for a global abolition of surrogacy through landmark case-law - MADANAMOOTHOO, Allane (Journal international de bioéthique et d’éthique des sciences, 2026)
Surrogacy, a practice whereby a woman carries a pregnancy for another person or couple, has become a lucrative global business that feeds on people’s desire to have a child. Despite its global popularity, surrogacy is a highly controversial biomedical practice. The Declaration of Casablanca of March 3, 2023 advocates a global abolition of surrogacy on the grounds that it contributes to the commodification of the surrogate mother and the surrogate-born child and violates their human dignity. The purpose of this paper is to support the Declaration of Casablanca through some landmark case-law from different jurisdictions.